DIGITAL ECOSYSTEMS FOR THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED BUSINESSES: OPPORTUNITIES AND RISKS - KULHANIK, Oksana; DAVYDIUK, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article highlights the features of digital ecosystems as an instrument of structural modernization of small and medium-sized businesses under conditions of economic transformation. The dynamics of the entrepreneurial sector in 2010–2024 are examined. It is found that wartime and post-crisis periods have significantly influenced the parameters of entrepreneurial activity, strengthening the micro-dominant structure of the sector. It is emphasized that digital ecosystems form adaptive architectures based on network effects, modularity and cooperation between business entities. It is underlined that the technological prerequisites for the functioning of such ecosystems include artificial intelligence, cloud services, and big data analytics, which ensure automation, personalization, and forecasting of market changes. It is stated that international digital platforms (such as Google Cloud, Microsoft Azure, Shopify, Stripe) create infrastructural opportunities for scaling the activities of small and medium-sized businesses and integrating them into global innovation networks. It is determined that Ukraine’s public policy is gradually shifting towards deepening the digital transformation of entrepreneurship, which is evidenced by the adoption of strategic documents and the development of the Diia.Business network. It is noted that OECD recommendations on the digital readiness of small and medium-sized enterprises aim to remove regulatory barriers, improve digital skills, and increase business participation in technological ecosystems. It is defined that practical examples of Ukrainian initiatives (in particular, the Digital Maturity Programme for SMEs) confirm the real application of the ecosystem approach in entrepreneurial activity. It is established that the development of digital ecosystems contributes to the reformatting of business models, strengthening network interaction, and forming data-driven managerial decisions. It is clarified that the effectiveness of ecosystems depends on the combination of technological innovations, institutional support mechanisms, and the ability of enterprises to adapt to digital challenges.
Keywords: digital ecosystems; digital transformation; entrepreneurship; small and medium-sized enterprises; public policy; digital platforms